Drivers of Soil Total Nitrogen and Phosphorus Storage in Alpine Wetland Across the Three Rivers Source Region on the Qinghai-Tibetan Plateau - Nie, Xiuqing; Wang, Dong; Zhou, Guoying; Xiong, Feng; Ren, Lining; Chen, Yongzhe; Ma, Kali; Zhong, Zebing; Du, Yangong (Frontiers in Environmental Science, 2022)
Although soil total nitrogen (STN) and soil total phosphorus (STP) play significant roles in terrestrial ecosystem function, their storage and driving factors in the alpine wetlands of the Tibetan Plateau remain unclear. In this study, we estimated STN and STP storage and their controlling factors, including vegetation, soil, and climate characteristics, using data collected from 50 sites across the wetlands in the Three Rivers Source Region. STN and STP storage in the top 30 cm of soil were 62.12 ± 37.55 Tg N and 9.24 ± 2.90 Tg P, respectively. Although STN density did not differ significantly for different vegetation types (i.e., alpine meadow and alpine wetland), belowground biomass showed a positive relationship with STN density. Mean annual precipitation (MAP) showed a significant positive relationship with STN density, whereas the effects of mean annual temperature on STN density were minor. Compared with the effects of vegetation and climatic factors, soil characteristics were found to not only exert a significant effect on STN density, but also influence the effects of climate and vegetation on STN density. For STP density, soil characteristics were found to be a significant controlling factor, whereas the effects of biomass and climatic factors were minor. The studied climate, soil, and vegetation characteristics jointly explained ~54% of STN variance, whereas soil characteristics explained only 20% of STP variation. MAP indirectly affected STN density via effects on vegetation and soil, and its direct effect on STN density was minor. This indicated a strong relationship between biotic and abiotic effects and STN density. Identification of the factors influencing STN and STP variance in alpine wetlands contributes to our understanding of the biogeochemical cycle in high-altitude regions.